Comparative study of La0.5Nd0.2Ca0.3–xKxMnO3 (x = 0.0 and 0.05) nanoparticles: Effect of A-cation size and calcination temperature. Issue 11 (1st August 2019) - Sharma, Narayan Dutt; Sharma, Suman; Choudhary, Nisha; Verma, Mukesh Kumar; Singh, Devinder
Abstract: In order to study the effect of sintering temperature and A-site cation radius on the structural, magnetic and transport properties, a systematic investigation of La0.5 Nd0.2 Ca0.3– x K x MnO3 ( x  = 0.0 and 0.05) nanoparticles has been undertaken. Rietveld analysis of X-ray diffraction data confirmed the presence of orthorhombic symmetry with Pbnm space group for all the samples. A paramagnetic-ferromagnetic transition is shown by all our investigated compounds. The materials exhibit semiconducting behavior and the metal-semiconductor transition temperatures ( T MS ) are found to be close to Curie temperatures ( T c ), indicating a strong correlation between their electrical and magnetic properties. Both T c and T MS of K-doped samples were found to be higher than their undoped counterparts at same calcination temperatures. In the high temperature region, it was observed that the resistivity data was best fitted by SPH model.